Clinical and Molecular Characteristics of A Novel Homozygous DNAJC3 Gene Variant in a Saudi family - Hussein Algahtani, Bader Shirah, Muhammad Imran Naseer, (Pakistan Journal of Medical & Health Sciences, 2024)
Combined cerebellar and peripheral ataxia with hearing loss and diabetes mellitus is an extremely rare neurodegenerative disorder affecting the central and peripheral nervous systems. The pathogenesis of widespread neurodegeneration in previously reported cases with homozygousDNAJC3mutations is proposed to be caused by a common etiology that is mitochondrial dysfunction and loss of mitigation of the endoplasmic reticulum stress response. In this paper, we reported a rare case of combined cerebellar and peripheral ataxia with hearing loss and diabetes mellitus in a Saudi family with a novel homozygous stop-gain mutation c.1177C>T p.(Arg393*) in exon 10 of the DNAJC3 gene, which creates a premature stop codon.The advances in genetic testing, including whole exome sequencing, have increased our knowledge of mitochondrial disorders, monogenic diabetes, and homozygous DNAJC3mutations phenotype who presents with juvenile-onset diabetes mellitus and multiple symptoms and signs of neurodegenerative disease, DNAJC3mutation should be suspected. Keywords: DNAJC3; Combined Cerebellar and Peripheral Ataxia with Hearing Loss and Diabetes Mellitus; Autosomal Recessive; Mutation; Saudi Arabia.